2020
DOI: 10.7554/elife.57063
|View full text |Cite
|
Sign up to set email alerts
|

Functionally specialized human CD4+ T-cell subsets express physicochemically distinct TCRs

Abstract: The organizational integrity of the adaptive immune system is determined by functionally discrete subsets of CD4+ T cells, but it has remained unclear to what extent lineage choice is influenced by clonotypically expressed T-cell receptors (TCRs). To address this issue, we used a high-throughput approach to profile the αβ TCR repertoires of human naive and effector/memory CD4+ T-cell subsets, irrespective of antigen specificity. Highly conserved physicochemical and recombinatorial features were encoded on a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 129 publications
(189 reference statements)
4
23
0
Order By: Relevance
“…TCRs of Treg cells exert relatively higher affinity to self-antigens, bind cognate pMHC ligands less specifically and have lower averaged energy of TCR-pMHC binding than Tfh cells that bind cognate pMHC ligands with high affinity and have a higher energy of TCR-pMHC binding, which agrees with previous data (52)(53)(54). At the same time, such differences were also observed in other subpopulations: amino acidic characteristics of the CDR3 loop among the populations Th1/Th1-17/Th17 were similar to the characteristics of Tfh, while among populations Th22/Th2a/Th2, there was a similarity with Treg cells (48). Besides, different subpopulations of T cells were distinguished by a diversity of TCR repertoires.…”
Section: Organization Of the Human T-cell Repertoiresupporting
confidence: 91%
See 4 more Smart Citations
“…TCRs of Treg cells exert relatively higher affinity to self-antigens, bind cognate pMHC ligands less specifically and have lower averaged energy of TCR-pMHC binding than Tfh cells that bind cognate pMHC ligands with high affinity and have a higher energy of TCR-pMHC binding, which agrees with previous data (52)(53)(54). At the same time, such differences were also observed in other subpopulations: amino acidic characteristics of the CDR3 loop among the populations Th1/Th1-17/Th17 were similar to the characteristics of Tfh, while among populations Th22/Th2a/Th2, there was a similarity with Treg cells (48). Besides, different subpopulations of T cells were distinguished by a diversity of TCR repertoires.…”
Section: Organization Of the Human T-cell Repertoiresupporting
confidence: 91%
“…The study of these parameters revealed the differences in the physicochemical properties of the CDR3 TCR loop at the level of different subpopulations of T cells. It was shown that Treg cells have TCRs with high cross-reactivity, while follicular helpers Tfh have TCRs with minimal cross-reactivity (48). TCRs of Treg cells exert relatively higher affinity to self-antigens, bind cognate pMHC ligands less specifically and have lower averaged energy of TCR-pMHC binding than Tfh cells that bind cognate pMHC ligands with high affinity and have a higher energy of TCR-pMHC binding, which agrees with previous data (52)(53)(54).…”
Section: Organization Of the Human T-cell Repertoiresupporting
confidence: 90%
See 3 more Smart Citations